2022
DOI: 10.1186/s12877-022-03363-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations of low handgrip strength and hand laterality with cognitive function and functional mobility – the Yishun Study

Abstract: Background Emerging evidence suggest that in addition to low hand grip strength (HGS), HGS asymmetry is associated with declining cognitive and physical functions. We examined the associations of low HGS and asymmetry with cognitive function and functional mobility in older adults. Methods Cross-sectional data of 330 community-dwelling adults (55.2% women) aged ≥ 55 years included HGS, Repeated Battery for the Assessment of Neuropsychological Statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…Our findings showed that HGS was significantly linked with a delayed learning ability and working memory, assessed by CERAD-DR and DSST, in stage 3-5 CKD patients. From the age over 65 years, a weaker HGS was associated with steeper declines in global cognitive function 29 , especially in memory and language domains in non-CKD without dementia population 30 . After adjustment for possible confounders, low muscle strength was associated with poorer performance in the delayed word recall test, verbal fluency test, and trail making test 31 , which are in line with our findings.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings showed that HGS was significantly linked with a delayed learning ability and working memory, assessed by CERAD-DR and DSST, in stage 3-5 CKD patients. From the age over 65 years, a weaker HGS was associated with steeper declines in global cognitive function 29 , especially in memory and language domains in non-CKD without dementia population 30 . After adjustment for possible confounders, low muscle strength was associated with poorer performance in the delayed word recall test, verbal fluency test, and trail making test 31 , which are in line with our findings.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have reported that there may be several mechanisms associated HGS asymmetry with physical performance, such as muscle mass asymmetry, neurodegenerative disorders (Z. Chen, Lee, et al, 2022), motoric cognitive risk syndrome (Verghese et al, 2019), brain hemisphere morbidity-related dysfunction (McGrath, Cawthon, et al, 2020), overcompensation and deficits in the mechanics due to acute and chronic (Oyanagi et al, 2023). Sleep quality and duration among middle-aged and older adults (Pana et al, 2021), and chronic kidney disease (Yang et al, 2023) were reported to be associated with a loss of skeletal muscle mass and muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…However, these risk factors can be partially explained based on existing research results. Previous studies have reported that there may be several mechanisms associated HGS asymmetry with physical performance, such as muscle mass asymmetry, neurodegenerative disorders (Z. Chen, Lee, et al, 2022), motoric cognitive risk syndrome (Verghese et al, 2019), brain hemisphere morbidity‐related dysfunction (McGrath, Cawthon, et al, 2020), overcompensation and deficits in the mechanics due to acute and chronic injuries (McGrath et al, 2022). Thus, physical conditions such as stroke and brain injury as well as loss of muscle mass and strength are risk factors for HGS asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…A prior study reported that the proportions of individuals with low HGS only, HGS asymmetry only, and asymmetric and low HGS were 16.4% 33.9%, and 12.1%, respectively, using the criteria of maximal dominant HGS < 28 kg (males) or < 18 kg (females) 27 to define low HGS. In the current study, we observed a similar proportion of 33.41% of the overall participants exhibiting HGS asymmetry only, but with lower proportions of low HGS only (5.63%) and asymmetry with low HGS (9.38%).…”
Section: Discussionmentioning
confidence: 99%